Icotinib alone or with bevacizumab as first‐line therapy in Chinese patients with advanced nonsquamous non‐small cell lung cancer and activating EGFR mutations: A retrospective study - Zhansheng Jiang; Jing Zhang; Haiyan Sun; Cong Wang; Yu Zhang; Yanyang Li; Zhanyu Pan (Thoracic Cancer, 2021)
Abstract Background This study focused on comparing the safety and therapeutic effects between icotinib monotherapy and icotinib plus bevacizumab combined therapy in non‐small cell lung cancer (NSCLC) cases harboring EGFR mutations. Methods Data were collected retrospectively from the Cancer Institute and Hospital of Tianjin Medical University between October 2018 and December 2019, where the NSCLC cases that harbored EGFR mutations underwent first‐line therapy with icotinib in the presence or absence of bevacizumab. This study included 90 cases, of which 60 patients were in the icotinib group (I) and 30 in the icotinib plus bevacizumab group (IB). Results The follow‐up period to evaluate median PFS in our study was 18 months. Median PFS was 18.0 months (95% confidence interval [CI]: 14.7–21.3) with icotinib plus bevacizumab and 11 months (95% CI: 8.9–13.1) with icotinib alone (hazard ratio 0·54, 95% CI: 0.31–0.92; p = 0.029). According to the subgroup analyses based on the type of EGFR genomic aberration, a prolonged median PFS was observed in the cases harboring exon 21 point mutation (Ex21.L858R) in the IB group compared to the I group (not reached vs. 11 months [8.8–13.2], p = 0.021). However, the difference between the cases harboring exon 19 deletions in the EGFR gene was not significant. The DCR and ORR were comparable between both groups. Substantially higher incidences of hypertension and proteinuria were observed in the combined group compared to the icotinib monotherapy group. Conclusions This is the first study to provide further evidence of the benefits of applying icotinib in combination with bevacizumab as first‐line treatment for advanced NSCLC cases harboring EGFR mutations. However, these findings need to be verified through prospective phase 3 clinical studies.